Professional Autonomy and IFRSS Adoption - Bogdan Dima; Ştefana Maria Dima; Miruna Năchescu; Chiara Saccon (Journal of Accounting and Management Information Systems (JAMIS), 2015)
Since the concept of professional judgment is at the core of principles-based financial reporting, the present article analyses the connection between professional autonomy (including as component professional judgment) and International Financial Reporting Standards (IFRSs) adoption. Thus, we developed a methodology for estimating the IFRSs' adoption status for 44 countries and constructed an Index of Professional Autonomy based on World Value Surveys. The levels of the respective index were estimated in an Exploratory Factor Analysis framework. In order to deal with the reverse causality issues, a GMM methodological framework was adopted. The results reveal that the overall index is positive and statistical significant at 1% related to IFRSs adoption. These findings are robust even if "the implication in voluntary work for professional associations" and the "importance of the material motivation of work" are considered as control variables.
Keywords: M48; 650; professional autonomy; professional judgment; IFRSs' adoption; principles-based; ruled-based